A rare complication of Nd-YAG capsulotomy: Propionibacterium acnes endopthalmitis - Chaudhry, M; Baisakhiya, S; Bhatia, MS (Nepalese Journal of Ophthalmology, 2011)
Posterior capsular opacification, also known as after cataract develops in 33 % of patients after uneventful cataract surgery. Nd-YAG Laser capsulotomy is the treatment of choice for PCO and is routinely performed by the general ophthalmologist on an OPD basis. Endophthalmitis, although a rare complication after Nd-YAG Laser capsulotomy, has been reported in the literature. We report a case of Propionibacterium acnes endophthalmitis following laser capsulotomy and the possible mechanism of its occurrence. Key words: PCO; Nd-YAG laser capsulotomy; propionibacterium acnes endophthalmitis  DOI: 10.3126/nepjoph.v3i1.4283Nepal J Ophthalmol 2011;3(5):80-82